Effects of self-help groups intervention on coping strategies of parents of children with Autism Spectrum Disorder (ASD) - Ridhoyanti Hidayah; Retno Lestari (Intelektual Pustaka Media Utama, 2019)
Coping strategies were significant predictors of psychosocial adaptation in parents of children with autism spectrum disorder (ASD). Self-help groups could be effective resources for parents in dealing with problems wile caring for children with ASD. The purpose of this study was to analyze the effects of self-help groups on coping strategies in parents of children with ASD. This study used pre and post quasi-experimental tests without a control group using self-help group interventions. There were thirty-three participants taken from the Malang City Autism Service Center using purposive sampling. Coping strategies based on cognitive and psychomotor abilities were measured using a questionnaire. The results showed paired t-test in all groups, at 5% significance level, statistically significant difference between mean score before and after self-help group interventions. Coping strategies in groups that received two supervised sessions and four times independently reached higher score compared to other groups. It can be concluded that it is important to implement self-help groups for parents who care for children with special needs.